MALPRAKTIK DOKTER DALAM PERSPEKTIF HUKUM - Bambang Heryanto (Jurnal Dinamika Hukum, 2010)
Now adays malpractice problem of health service start to talk lively by the various society. That matter is seen from many indictment cases of malpractice which submitted by the society about a doctor profession that regarded to have inflicted the patient in conducting a task which are cause the wrong act, feel pain, injury, physical defect, body damage, and death. A law justification of doctor malpractice which is cause the inflicted of patient, so the victim side could be demand for materil and immateril compensation. The law protection of doctor malpractice’s victim who is demand to the court, a judges could apply a Res Ipsa Loquitur doctrine, its means that the victim sides does not need to prove the presence of carelessness substances, but they enough to show the truth.Keyword: Malpractice, Res Ipsa Loquitur